2019
DOI: 10.3390/antiox8060187
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Markers of Oxidative Stress in Children with Autism Spectrum Disorder (ASD)

Abstract: Background: Autism spectrum disorder (ASD) is a developmental disorder characterized by deficits in social interaction, restricted interest and repetitive behavior. Oxidative stress in response to environmental exposure plays a role in virtually every human disease and represents a significant avenue of research into the etiology of ASD. The aim of this study was to explore the diagnostic utility of four urinary biomarkers of oxidative stress. Methods: One hundred and thirty-nine (139) children and adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The learning strategy of SVM is spacing maximization, which can be formalized as a problem of solving convex quadratic programming [21]. This algorithm has been widely used to build the prediction models using the data of blood test [22,23] and urine test [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…The learning strategy of SVM is spacing maximization, which can be formalized as a problem of solving convex quadratic programming [21]. This algorithm has been widely used to build the prediction models using the data of blood test [22,23] and urine test [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a negative correlation was seen between SOD activity, urinary 8-oxodG, and respiratory burst intensity in peripheral blood polymorphonuclearleucocytes in ASD participants. However, other studies have shown positive associations between serum and urinary 8-oxodG and ASD severity (Osredkar et al 2019 ), and diagnosis (Metwally et al 2018 ), respectively.…”
Section: Resultsmentioning
confidence: 91%
“…This compound has long been thought to be the explanation of the "French Paradox", which consist in a lower incidence of cardiovascular disease despite a high saturated fat diet for its antioxidant properties and multidrug activities [51]. Oxidative stress is deeply involved in ASD pathology [52] because this dysregulation has been found and studied also as a possible biomarker in blood and urine [53][54][55]. There are reports that show the reduction in reduced glutathione, the major endogenous antioxidant, in several brain regions associated with communication, memory, sensory and motor coordination [45,56].…”
Section: Discussionmentioning
confidence: 99%